Thulium-doped fiber laser with switchable single-wavelength output using polarization-dependent loss - Guan, Biao; Yan, Fengping; Qin, Qi; Liu, Yan; Yang, Dandan; Tan, Haoyu; Li, Ting; Yu, Chenhao; Wang, Xiangdong; Jiang, Youchao; Kumamoto, Kazuo; Suo, Yuping (Frontiers in Physics, 2023)
A thulium-doped fiber laser (TDFL) with switchable single-wavelength output was proposed and experimentally constructed, and its output characteristics were investigated. The central wavelengths were 1940.52 nm and 2048.04 nm, defined by a superimposed uniform fiber Bragg grating (SI-UFBG) with reflectivity larger than 92%. Switchable output was successfully achieved by using polarization-dependent loss, with the help of a drop-in polarization controller and an in-line polarizer. For both output wavelengths, optical signal-to-noise ratios larger than 80 dB were achieved. Maximum fluctuations of the central wavelengths of 1940.52 nm and 2048.02 nm under 60 minutes were, respectively, 0.04 nm and 0.01 nm. Maximum fluctuations of output power for the same wavelengths over the same time period were, respectively, 1.09 dB and 0.12 dB. Maximum output powers of 215.12 mW and 155.53 mW were achieved for the respective output wavelengths of 1940.52 nm and 2048.02 nm. Moreover, a tuning range of 2 nm was realized by enforcing a strain on the SI-UFBG. The proposed TDFL may be applied in laser medicine and free-space-related applications.